Substitusi Konsentrat Protein Menggunakan Tepung Bulu Ayam yang Diolah Secara Fisiko-Kimia dan Fermentasi Menggunakan Bacillus sp. Mts - Sri Rahayu; Muhamad Bata; Winarto Hadi (Agricultural Faculty, 2014)
(Protein concentrate substitution using feather meal processed by physico-chemistry and fermentatio)ABSTRACT. The objective of this research was to evaluate the effect of protein concentrate substitution using processed feather meal in growing layer-ration. Chicken feather meal was processed by physico-chemical techniques viz.soaking in 0.5% (b/v) NaOH and Na2S at 60C and continued by fermentation using Bacillus sp. MTS. The method was experimental method with a Completely Randomized Design with five treatments that replicated for four times. The treatments tested was level of concentrate substitution i.e. 0, 4, 8, 12 and 16%. Protein concentrate substitution had no significantly effect (P 0.05) on growth, feed consumption and convertion of growing layer. Keratin meal from chicken feather can be applied in growing layer-ration 16% respectively or substitute the protein concentrate as much as 53%.